STRATEGI PEMASARAN DIGITAL DALAM MENINGKATKAN VOLUME PENJUALAN PADA AMANDA CAFE DI ERA REVOLUSI INDUSTRI 4.0 - Miftahol Arifin; Moh Kurdi; Syaiful Anwar (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2021)
This researchis motivated by the instability of sales in recent monts at Amanda cafe. So it is necessary to implement a strategy where the strategy is in accordance with the current era of digital strategies. This study aims to find out what are the obstacles in increasing sales volume at Amanda cafe and what strategies are applied in the café. This study uses qualitative research methods that describe Digital Marketing Strategies in Increasing Sales Volume at the Amanda cafe in the Industrial Revolution Era 4.0. and data in the field with interviews with informants, observation guidelines and dokumentation in the field that has been predetermined. The results of this study, are described throught various information and data findings in the field during the study, regarding Digital Marketing Strategies in Incresing Sales Volume at Amanda cafe in the Industrial Revolution Era 4.0.